Promoting Innovation in Mathematics Learning: An International Program for Strengthening Teacher Competence through STEAM - Akhsanul In'am; Moh Mahfud Effendi; Reni Dwi Susanti; Marhan Taufik; Hendarto Cahyono (Jurnal Pengabdian UNDIKMA, 2026)
This community service activity aims to strengthen teachers’ competencies in designing and implementing contextual STEAM learning that is aligned with local school conditions. The program was conducted at the Musa-Asia Integrated School (SEPAMA), Cambodia, involving junior high school teachers and school leaders. The implementation methods included a baseline needs analysis, workshop-based training, instructional design mentoring, the implementation of simple classroom projects, and pre-test and post-test evaluations of teacher competency. Data were analyzed descriptively and quantitatively by comparing the mean pre-test and post-test scores and calculating the gain. The findings indicate an improvement in teacher competency across all measured dimensions, particularly in interdisciplinary integration and project-based learning. The average score for STEAM understanding increased from 2.82 to 3.27, representing a 15.96% improvement, while the project-based learning score increased from 2.45 to 3.09, representing a 26.12% improvement. Teachers also began to perceive STEAM learning as a practical and feasible approach that could be implemented by utilizing the school environment and students’ daily activities. The classroom project implementation demonstrated increased student engagement, although not all teachers applied the approach consistently due to time constraints and the need for further adaptation. Field findings suggest that the simplified contextual STEAM approach is relevant to local school settings and effective in enhancing teacher readiness. Overall, this activity had a positive impact on improving teacher capacity and learning quality, with strong potential for sustainability through continuous mentoring and institutional support from partner schools.